Undocumented worker employment and firm survivability - J. David Brown; Julie L. Hotchkiss; Myriam Quispe-Agnoli (Federal Reserve Bank of Atlanta, 2008)
Do firms employing undocumented workers have a competitive advantage? Using administrative data from the state of Georgia, this paper investigates the incidence of undocumented worker employment across firms and how it affects firm survival. Firms are found to engage in herding behavior, being more likely to employ undocumented workers if competitors do. Rivals' undocumented employment harms firms' ability to survive while firms' own undocumented employment strongly enhances their survival prospects. This finding suggests that firms enjoy cost savings from employing lower-paid undocumented at workers wages less than their marginal revenue product. The herding behavior and competitive effects are found to be much weaker in geographically broad product markets, where firms have the option to shift labor-intensive production out of state or abroad.
Keywords: L1; J23; J61; 330; undocumented workers; firm dynamics; monopsony; immigration policy; Schwarzarbeit; Internationale Arbeitsmobilität; Illegale Einwanderung; Wettbewerbsvorteil; Wettbewerbsstrategie; Herdenverhalten; Theorie; Schätzung